2008
DOI: 10.1128/jvi.01444-07
|View full text |Cite
|
Sign up to set email alerts
|

Subtype-Specific Conformational Differences within the V3 Region of Subtype B and Subtype C Human Immunodeficiency Virus Type 1 Env Proteins

Abstract: The V3 region of the human immunodeficiency virus type 1 gp120 Env protein is a key domain in Env due to its role in interacting with the coreceptors CCR5 and CXCR4. We examined potential subtype-specific V3 region differences by comparing patterns of amino acid variability and probing for subtype-specific structures using 11 anti-V3 monoclonal antibodies (V3 MAbs). Differences between the subtypes in patterns of variability were most evident in the stem and turn regions of V3 (positions 9 to 24), with the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
54
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 83 publications
10
54
2
Order By: Relevance
“…They examined HIV-1 clade C-infected individuals, naĂŻve for antiretroviral therapy, at different disease stages, in order to characterize the V1 to V5 variable regions with respect to sequence length, glycosylation pattern and net electric charge. In the chronic stage of the disease, they observed in the V1, V2 and V4 loops, an increase in sequence length, amino acid variability and putative N-glycosylation sites but very little change in the V3 loop as reported previously for clade C [44]. These data suggest that the V1 and V4 loops are likely to be the main drivers of clade C HIV-1 virus evolution which agrees with the finding that the V4 loop is a major target of neutralization activity in clade C infections [45].…”
supporting
confidence: 76%
“…They examined HIV-1 clade C-infected individuals, naĂŻve for antiretroviral therapy, at different disease stages, in order to characterize the V1 to V5 variable regions with respect to sequence length, glycosylation pattern and net electric charge. In the chronic stage of the disease, they observed in the V1, V2 and V4 loops, an increase in sequence length, amino acid variability and putative N-glycosylation sites but very little change in the V3 loop as reported previously for clade C [44]. These data suggest that the V1 and V4 loops are likely to be the main drivers of clade C HIV-1 virus evolution which agrees with the finding that the V4 loop is a major target of neutralization activity in clade C infections [45].…”
supporting
confidence: 76%
“…Previously, we along with others have demonstrated that HIV-2 Env could be used as a scaffold to present HIV-1 MPER and CD4i epitopes in the context of a functional glycoprotein and that such viruses could serve as sensitive and specific probes for HIV-1-elicited epitope-specific NAbs (18,19,34,61,102 In the present study, we focused on HIV-1 V3, which continues to attract substantial attention as a target of NAbs (2,54,72,74,76,99,107). Mamounas and colleagues first demonstrated that a chimeric virus containing an HIV-2 backbone and an HIV-1 MN V3 loop was capable of infecting human T cells and showed susceptibility to HIV-1 V3-specific antiserum (64).…”
Section: Discussionmentioning
confidence: 98%
“…A third strategy has been to make site-directed mutations in NAb epitopes in Env glycoproteins and to use these proteins as probes in binding, absorption, or infectivity experiments (54,61,62,72). A fourth approach has been to make reciprocal exchanges between homologous regions of different HIV-1 Env glycoproteins to look for gain or loss of NAb sensitivity (54,68,76,86,87,89). The last three approaches share a common limitation in that V3 neutralizing activity is analyzed against a backdrop of other HIV-1 gp120/41 neutralizing reactivities, making a clear dissection of V3-specific NAb activity challenging.…”
mentioning
confidence: 99%
“…Such diversity in the amino acid sequence may affect the protein structure; thus, we cannot rule out the possibility that the structure of Env gp120 is somewhat different among diverse HIV-1 subtypes. Indeed, structural differences of the conserved and variable regions of gp120 are reported to exist between subtype B and C viruses (11,33). The b12 antibody recognizes a conformational epitope; thus, b12 susceptibility of HIV-1 Env is necessarily affected by the protein structure of gp120.…”
Section: Discussionmentioning
confidence: 99%